2013
DOI: 10.1063/1.4804262
|View full text |Cite
|
Sign up to set email alerts
|

Broadband enhancement of spontaneous emission from nitrogen-vacancy centers in nanodiamonds by hyperbolic metamaterials

Abstract: We experimentally demonstrate a broadband enhancement of emission from nitrogen-vacancy centers in nanodiamonds. The enhancement is achieved by using a multilayer metamaterial with hyperbolic dispersion. The metamaterial is fabricated as a stack of alternating gold and alumina layers. Our approach paves the way towards the construction of efficient single-photon sources as planar on-chip devices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…Plasmonic nanorod metamaterials possess unique optical properties making them unrivalled for applications in imaging , sensing , ultrasound detection , designing nonlinear optical properties and controlling quantum optical processes . These metamaterials exhibit hyperbolic isofrequency surfaces in a spectral range where the real part of the diagonal components of the permittivity tensor, corresponding to ordinary and extraordinary axis, have opposite signs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmonic nanorod metamaterials possess unique optical properties making them unrivalled for applications in imaging , sensing , ultrasound detection , designing nonlinear optical properties and controlling quantum optical processes . These metamaterials exhibit hyperbolic isofrequency surfaces in a spectral range where the real part of the diagonal components of the permittivity tensor, corresponding to ordinary and extraordinary axis, have opposite signs.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic nanorod metamaterials possess unique optical properties [2] making them unrivalled for applications in imaging [4], sensing [5,6], ultrasound detection [7], designing nonlinear optical properties [8][9][10] and controlling quantum optical processes [11,12]. These metamate-Department of Physics, King's College London, Strand, London, WC2R 2LS, UK * Corresponding author: e-mail: nikolaos.vasilantonakis@kcl.ac.uk…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that the emission from multiple NV centers in nanodiamonds could be enhanced over a broad wavelength range by using multilayer hyperbolic metamaterials, fabricated as a stack of alternating layers of gold and alumina . In this work, we report the next step towards the construction of an efficient on‐chip CMOS‐compatible single‐photon source by replacing gold with semiconductor‐compatible plasmonic ceramics as an HMM material building block.…”
Section: Introductionmentioning
confidence: 98%
“…For the perfect planar HMM structure, the excitation in these modes is eventually lost to absorption. However, since it is possible to outcouple these metamaterial modes into free space, they could significantly contribute to the emission signal [44,47] Previously, we have shown that the emission from multiple NV centers in nanodiamonds could be enhanced over a broad wavelength range by using multilayer hyperbolic metamaterials, fabricated as a stack of alternating layers of gold and alumina [48]. In this work, we report the next step towards the construction of an efficient on-chip CMOS-compatible single-photon source by replacing gold with semiconductor-compatible plasmonic ceramics [49,50] as an HMM material building block.…”
mentioning
confidence: 99%
“…Previously, we have shown that the emission from multiple NV centers in nanodiamonds can be enhanced over a broad range by multilayer hyperbolic metamaterials, fabricated as a stack of alternating layers of gold and alumina [3]. In this work, we extend our previous study towards the construction of an efficient on-chip singlephoton source.…”
Section: Experimental Set-up and Sample Detailsmentioning
confidence: 69%